Translation and preliminary validation of the “Incharge Financial Distress/ Financial Well-Being Scale” for brazilian portuguese (Research, Society and Development, 2021)
Financial stress, commonly generated after scenarios and subsequent economic crises, contributes negatively to the psychosocial scenario and to public health. The aim of this study was to translate, linguistic and cross-cultural adaptation of the "In Charge Financial Distress/ Financial Well-Being Scale." into the Brazilian Portuguese language. The main steps recommended by the World Health Organization for questionnaires validations were followed. The pre-test was performed in a sample of 49 participants. For the preliminary verification of reliability and internal consistency, the Concordance Correlation Coefficient (CCC), Cohen's Kappa index, and Cronbach's Alpha were used in 60 volunteers between 18 and 60 years of age. The reliability of the scale by test-retest was strong (CCC=0.73). In addition, it was found a good internal consistency (α=0.878). The Portuguese version presents linguistic and cultural equivalence in relation to the original instrument, and can be applied for research purposes in the assessments of financial stress levels.